The promise of a nonhuman turn for CIFC scholarship. Issue 4 (2nd October 2019) - Allen, Jordan; Allen, Nicole
ABSTRACT: Maintaining an immaterial and modernist approach to interpersonal and family relationships obscures places in lived experiences where scholarly critiques may be most disruptive and impactful. Nonhuman vocabularies provide valuable foundations for critical interpersonal and family (CIFC) scholars, as we analyze and disrupt problematic communication practices that constitute contested interpersonal and family relationships. We argue that it is incumbent upon CIFC researchers to critique the material-discursive practices that constitute unjust operations of power by including and recognizing nonhuman actants in our analyses and subsequent critiques. In this paper, we first describe current barriers that keep CIFC scholars from reaching for nonhuman vocabularies. Second, we identify 3 nonhuman theories CIFC scholars could adopt. Finally, we discuss the risks and promises of nonhuman approaches for CIFC scholars.